Looking at the bigger picture: effect of performance-based contracting of district health services on equity of access to maternal health services in Zambia - Chansa, Collins; Mukanu, Mulenga Mary; Chama-Chiliba, Chitalu Miriam; Kamanga, Mpuma; Chikwenya, Nicholas; Bellows, Ben; Kuunibe, Naasegnibe (Health policy and planning, 2020)
Abstract. Zambia has been using output-based approaches for over two decades to finance whole or part of the public health system. Between 1996 and 2006, perfo
Advance access publication date: 29 October 2019
Gesehen am 14.04.2020